Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Technical Note on Crisis Management and Bank Resolution Frameworks. (IMF Staff Country Reports; Country Report, 2011)
The global financial crisis hit the Netherlands' financial sector hard. This note analyzes the Dutch framework for crisis management and bank resolution, and formulates recommendations to address observed weaknesses. The overall framework for official financial support to stem systemic crisis is appropriate. The current framework for resolving ailing banks in going could be strengthened considerably. The framework for the orderly liquidation of banks could be strengthened and fine-tuned. The deposit guarantee scheme (DGS) has a number of helpful characteristics, but could be significantly enhanced.